Velisoptera taschi nov.gen., nov.sp. a Carboniferous Insect from Bajo de Velis, Argentina - PINTO, IRAJÁ DAMIANI; ADAMI-RODRIGUES, KAREN (Pesquisas em Geociências, 1997)
The monotypic Velisoptera taschi, nov. gen., nov. sp. is another new pterygote insect from the Pallero member of the Bajo de Velis formation, Upper Carboniferous, Argentina. It represents a new family, Velisopteridae, of the Diaphanopterodea.